2006
DOI: 10.1126/science.1121325
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Effect of GABAergic Axo-Axonic Cells in Cortical Microcircuits

Abstract: Axons in the cerebral cortex receive synaptic input at the axon initial segment almost exclusively from gamma-aminobutyric acid-releasing (GABAergic) axo-axonic cells (AACs). The axon has the lowest threshold for action potential generation in neurons; thus, AACs are considered to be strategically placed inhibitory neurons controlling neuronal output. However, we found that AACs can depolarize pyramidal cells and can initiate stereotyped series of synaptic events in rat and human cortical networks because of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
556
5
16

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(615 citation statements)
references
References 27 publications
32
556
5
16
Order By: Relevance
“…Furthermore, all four successfully reconstructed cells exhibiting feedback excitation had axons confined to the BL, and all exhibited closely spaced rows of boutons, or axonal cartridges. These cartridges are a hallmark of axoaxonic cells in cortex, hippocampus, and amygdala (Howard et al, 2005;Muller et al, 2005), the type of interneuron that has recently been reported to directly excite cortical layer 2/3 pyramidal neurons to threshold (Szabadics et al, 2006). Thus, given the similarity of this finding to that reported for cortical AACs, and the lack of a plausible alternative explanation, we suggest that AACs of the BL can also directly depolarize local principal neurons to threshold.…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…Furthermore, all four successfully reconstructed cells exhibiting feedback excitation had axons confined to the BL, and all exhibited closely spaced rows of boutons, or axonal cartridges. These cartridges are a hallmark of axoaxonic cells in cortex, hippocampus, and amygdala (Howard et al, 2005;Muller et al, 2005), the type of interneuron that has recently been reported to directly excite cortical layer 2/3 pyramidal neurons to threshold (Szabadics et al, 2006). Thus, given the similarity of this finding to that reported for cortical AACs, and the lack of a plausible alternative explanation, we suggest that AACs of the BL can also directly depolarize local principal neurons to threshold.…”
Section: Discussionmentioning
confidence: 34%
“…Recently, cortical axoaxonic interneurons (AACs) that make "chandelier" synapses on the axon initial segment of pyramidal neurons (Howard et al, 2005) have been found to depolarize local pyramidal neurons because of a positively shifted GABA A reversal potential at the axon initial segment (Szabadics et al, 2006). Chandelier synapses have also been described in the amygdala, and these terminals are known to express parvalbumin (Kemppainen and Pitkanen, 2000;McDonald and Betette, 2001;Muller et al, 2006).…”
Section: Interneurons Evoke Feedback Glutamatergic Excitationmentioning
confidence: 99%
“…However, as long as we are uncertain about the exact local membrane potentials and chloride concentration in the mitral cell dendrites, we cannot determine whether the inputs from the granule cells are actually inhibitory, for with lower membrane potential below the chloride equilibrium potential (58 log [Clex]/ [Clin]) or with higher intracellular chloride, the action of GABA is excitatory (Szabadics et al, 2006). Assuming GABA to be inhibitory, we consider two possibilities to explain its role in promoting plasticity.…”
Section: Acetylcholine May Facilitate Pheromonal Memory Formationmentioning
confidence: 99%
“…Unlike organic Cl − dyes (Verkman, 1990), Clomeleon expression can be targeted to distinct populations of neurons. These properties make Clomeleon suitable for studying many poorly understood aspects of [Cl − ] i regulation, including activity-dependent ionic plasticity (Kaila, 1994;Payne et al, 2003), compartmental gradients of [Cl − ] i (Duebel et al, 2006;Szabadics et al, 2006), sensory signal transduction (Reuter et al, 1998), and pathophysiological mechanisms in a multitude of diseases (Payne et al, 2003;Pond et al, 2006).…”
Section: Introductionmentioning
confidence: 99%